Traffic Simulation with Open-Source and Commercial Traffic Microsimulators: A Case Study - Nelson Baza-Solares; Ruben Velasquez-Martínez; Cristian Torres-Bohórquez; Yerly Martínez-Estupiñán; Cristian Poliziani (Communications - Scientific letters of the University of Zilina, 2022)
The analysis of traffic problems in large urban centers often requires the use of computational tools, which give the possibility to make a more detailed analysis of the issue, suggest solutions, predict behaviors and, above all, support efficient decision-making. Transport microsimulation software programs are a handy set of tools for this type of analysis. This research paper shows a case study where functions and limitations of Aimsun version 8.2.0, a commercial-like European software and Sumo version 1.3.1, a European open-source software, are presented. The input and output data are similar in both software and the interpretation of results is quite intuitive for both, as well. However, Aimsun's graphical interface interprets results more user-friendly, because Sumo is an open-access software presented as an effective alternative tool for transport modeling.